Upgrading a wastewater treatment plant with thermophilic digestion of thermally pre-treated secondary sludge: techno-economic and environmental assessment. (1st September 2015) - Gianico, Andrea; Bertanza, Giorgio; Braguglia, Camilla Maria; Canato, Matteo; Laera, Giuseppe; Heimersson, Sara; Svanström, Magdalena; Mininni, Giuseppe
Abstract: Nowadays, several technologies and management strategies are proposed for upgrading wastewater treatment plants (WWTPs) in order to improve sludge stabilization or minimize sludge production. In order to make sure that this leads to overall improvements, their techno-economic and environmental performance has to be carefully evaluated. In response to this, the techno-economic and environmental performance was assessed for a considered model reference WWTP upgraded with separate treatment and disposal for primary and secondary sludge to provide guidance to research, policy and investment efforts. This paper departs in an experimental campaign carried out within the EU project "ROUTES" and describes an assessment of an upgrade of a WWTP, involving wet oxidation of primary sludge and thermophilic anaerobic digestion (integrated with thermal hydrolysis pre-treatment) for secondary sludge. The reference plant and the upgrade implied different disposal routes for the resulting sludges: incineration for the stabilized sludge deriving from the reference WWTP; agricultural land application for the secondary stabilized sludge from the upgraded plant and landfilling for the solid residue deriving from the wet oxidation process (as non-hazardous waste). The mass balance carried out for both reference and upgraded WWTPs showed a reduction of total sludge production (up to 45%) for the upgraded WWTP. The additional energy demand of the upgraded solution (+22.4 Wh/(PE d), PE: population equivalent) was partially balanced by the electric energy produced by combined heat and power unit installed in the upgraded WWTP (−18.08 Wh/(PE d)). The integrated assessment showed that the upgraded solution, although resulting in an increase of WWTP technical complexity, may contribute to environmental and economic advantages. The paper provides guidance in terms of which aspects need a more thorough evaluation when this upgrade is considered in real cases. Highlights: An integrated assessment of wastewater treatment plant (WWTP) upgrade was performed. The full-scale feasibility of an innovative sludge treatment was assessed. Sludge production and disposal costs were significantly reduced after WWTP upgrade. The higher energy demand was balanced with electric energy generated after upgrade. For all LCA impact categories, the upgraded system performs similar to the reference.